2014
DOI: 10.1007/s11033-014-3767-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IGF1, GH, and PIT1 markers on the genetic parameters of growth and reproduction traits in Canchim cattle

Abstract: The availability of dense genomic information has increased genome-wide association studies for the bovine species; however research to assess the effect of single genes on production traits is still important to elucidate the genes functions. On this study the association of IGF1, GH, and PIT1 markers with growth and reproductive traits (birth weight, weaning weight, weight at 12 and 18 months of age, preweaning average daily weight gain, age and weight at first calving, and scrotal circumference at 12 and 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Therefore the frequency of the V allele was lower than the L allele (87.045 vs. 12.955). Allele and genotype frequencies for the GH-AluI polymorphisms given in this work were in agreement with those reported in previous studies, which have been discussed extensively in Holstein dairy cows (Balogh et al, 2009b;Ruprechte et al, 2011;Grossi et al, 2015). However, other findings have shown the dominance of the heterozygous genotype LV and the absence of the homozygous genotype VV (Aruna et al, 2004;Hadi et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore the frequency of the V allele was lower than the L allele (87.045 vs. 12.955). Allele and genotype frequencies for the GH-AluI polymorphisms given in this work were in agreement with those reported in previous studies, which have been discussed extensively in Holstein dairy cows (Balogh et al, 2009b;Ruprechte et al, 2011;Grossi et al, 2015). However, other findings have shown the dominance of the heterozygous genotype LV and the absence of the homozygous genotype VV (Aruna et al, 2004;Hadi et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, no obvious association of GH with AGE_1CALV and CI was observed in Canchim and Hungarian Holstein-Friesian cattle (Kovacs et al, 2006;Grossi et al, 2015) and with AGE_1CALV in a Hungarian Holstein-Friesian bull dam population (Katalin et al, 2006). Moreover, Kovacs et al (2006) reported no noteworthy effect of GH-AluI on the CI, the number of calves or the dry period in a Hungarian Holstein-Friesian bull dam.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The IGF1 pathway influence gonadotrophin‐releasing hormone (GnRH) neurons during the puberty and it is directly associated with the puberty progression and the development of reproductive traits [ 52 , 63 , 64 ]. Additionally, IGF1 was associated with the regulation of several production traits, for example, feed intake, feed conversion, body weight, milk protein yield, milk fat yield, milk fat concentration and somatic cell score [ 65 – 67 ]. Variants mapped on IGF1R may result in a change of affinity between IGF1 and its receptor, resulting in a different response to the circulating levels of this hormone.…”
Section: Resultsmentioning
confidence: 99%
“…This included: OBSL1-a cytoskeletal adaptor protein previously associated with body size in humans (Hanson et al 2009) and cetaceans (Sun et al 2019); and IGF1R-a transmembrane receptor of insulin-like growth factor 1 (IGF1). The IGF1 pathway has a well-known role in body size scaling in a range of taxa, including chickens (Beccavin et al 2001;Beckman et al 2003), cattle (Grossi et al 2015), brown house snakes (Sparkman et al 2010) and dogs (Sutter et al 2007); and has been previously associated with bill size in the black-bellied seedcracker (onHoldt et al 2018). RUNX3-which, in the zebrafish, modulates bone morphogenetic protein (BMP) signalling during craniofacial development (Dalcq et al 2012).…”
Section: Candidate Genesmentioning
confidence: 99%